2018
DOI: 10.1063/1.5051598
|View full text |Cite
|
Sign up to set email alerts
|

High-order harmonic generation from 2D periodic potentials in circularly and bichromatic circularly polarized laser fields

Abstract: We studied the high-order harmonic generation (HHG) from 2D solid materials in circularly and bichromatic circularly polarized laser fields numerically by simulating the dynamics of single-activeelectron processes in 2D periodic potentials. Contrary to the absence of HHG in the atomic case, circular HHGs below the bandgap with different helicities are produced from intraband transitions in solids with C 4 symmetry driven by circularly polarized lasers. Harmonics above the bandgap are elliptically polarized due… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…The last decade has marked the first experimental observations of solid-state HHG 12,13,[17][18][19]24 , which in turn have sparked off extensive theoretical works (e.g. 27,[35][36][37][38][39][40] ) to further understand the origin of the process and to investigate the possibility of enhancing its efficiency. These theoretical considerations were mostly focused on HHG from bulk semiconductors, in which the electron wavepacket is initially delocalised over bulk states.…”
Section: Introductionmentioning
confidence: 99%
“…The last decade has marked the first experimental observations of solid-state HHG 12,13,[17][18][19]24 , which in turn have sparked off extensive theoretical works (e.g. 27,[35][36][37][38][39][40] ) to further understand the origin of the process and to investigate the possibility of enhancing its efficiency. These theoretical considerations were mostly focused on HHG from bulk semiconductors, in which the electron wavepacket is initially delocalised over bulk states.…”
Section: Introductionmentioning
confidence: 99%
“…2 c, f), the harmonic emission from the linearly-polarized fundamental exhibits the expected, fourfold pattern, while for excitation with the bi-circular field the signal loses the appearance of its fourfold symmetry. The convolution of the threefold field and the fourfold crystal should result in a 12-fold signal 38 , which is not resolvable. Since in MgO(111) the angular-dependent emission peaks are narrow enough to resolve a 12-fold symmetry, we conclude that the MgO(100) is more isotropic.…”
Section: Resultsmentioning
confidence: 99%
“…2c and 2f), the harmonic emission from the linearly-polarized fundamental exhibits the expected, 4-fold pattern, while for excitation with the bi-circular field the signal loses the appearance of its 4-fold symmetry. The convolution of the 3-fold field and the 4-fold crystal should result in a 12-fold signal 31 , which is not resolvable with our setup.…”
Section: Inversion-symmetry Probingmentioning
confidence: 95%
“…There have been many efforts in experiment and theory that are devoted to achieving circularly polarized HHG and attosecond pulses in atoms. Recently, harmonics from degenerate current-carrying orbitals by bichromatic counterrotating circularly polarized pulses have been studied . HHG from 2D solid materials by bicircular fields has been proposed, and it is found that the harmonic polarization depends on the bandgap. Bichromatic elliptically and circularly polarized pulses have been also used to produce linearly polarized attosecond pulses, , electron vortices, ultrafast magnetic pulses, , significant nonsequential double ionization, , above threshold ionization, and visualization of quantum interference between degenerate magnetic states .…”
Section: Introductionmentioning
confidence: 99%